The case against zoning. Issue 4 (27th July 2021) - Block, Walter; Huddell, Sarah
Abstract : Purpose: This paper aims to examine the case against land use zoning. Design/methodology/approach: We approach this analysis from the perspective of economics, health and geography. Findings: The findings of this paper suggest that the case against zoning is overwhelming. Research limitations/implications: This result applies only to public zoning, not the private variety thereof. Practical implications: Public zoning should be repealed. Originality/value: This paper approaches this from three perspectives: economics, health and geography; this has not been done before.